Rootstocks for Florida Stone Fruit - Mercy Olmstead; Jose Chaparro; James Ferguson (EDIS)
Rootstocks have been used in many tree fruit systems to provide growth advantages or pest or disease resistance without affecting productivity and fruit quality. In Florida, stone fruit are grown on rootstocks that specifically provide pest resistance to the peach root-knot nematode. Although several root-knot nematode-resistant rootstocks are available for stone fruit grown in other locations and climates, ‘Flordaguard’ peach rootstock is currently recommended for stone fruit production in Florida. This revised 5-page fact sheet was written by M. Olmstead, J. Chaparro, and J. Ferguson, and published by the UF Department of Horticultural Sciences, November 2012.